Happy or not? An investigative study on well-being and anhedonia in everyday life - Sarah A. Merklein; Jutta Peterburs; Annakarina Mundorf (PLoS ONE, 2025)
Anhedonia, the inability to experience pleasure or interest in activities, is a key symptom across various psychiatric disorders, including depression. It links to poor quality of life, higher suicide risk, and poorer prognosis. While anhedonia is often studied in clinical populations, its prevalence in healthy individuals and its dimensional nature remain underexplored. This study examined the prevalence of anhedonia in 128 German university students, comparing those with and without psychiatric symptoms and modeling psychiatric symptoms as predictor of anhedonia, measured with the Dimensional Anhedonia Rating Scale (DARS). Results showed that the clinical group demonstrated relatively low levels of anhedonia (total DARS-26: 85.03 ± 12.88) that did not differ from the healthy group (88.80 ± 7.88). Considerable variability suggests that a purely categorical approach to anhedonia may not capture its full complexity. Multiple regression analyses revealed that negative symptoms (e.g., affective flattening) were the strongest predictor of anhedonia, both in the full (b = −0.54, p < .001) and within the (sub-)clinical sample (b = −0.64, p < .001). Anxiety was also a significant predictor in the (sub-)clinical group (b = −1.06, p = .01), underscoring its impact on reward processing. Depression did not emerge as a strong predictor (b = −0.21, p = .49) when considered alongside other variables, indicating that its link to anhedonia may be mediated by other factors. Multigroup confirmatory factor analysis of the DARS showed that the 17-item version provided a better fit than the 26-item version, reinforcing the shorter version as a more efficient tool for assessing anhedonia. Taken together, the present findings support the use of a dimensional approach to anhedonia, which offers a more nuanced view of the underlying psychological and neurological mechanisms. Future research should explore anhedonia in larger, diverse samples for a comprehensive understanding of the link between anhedonia and mental illness. Registration: The study was pre-registered on OSF: https://doi.org/10.17605/OSF.IO/234A7.